Acceptability of Financial Incentives for Health Behaviours: A Discrete Choice Experiment. - Emma L Giles; Frauke Becker; Laura Ternent; Falko F Sniehotta; Elaine McColl; Jean Adams (PLoS ONE)
Background Healthy behaviours are important determinants of health and disease, but many people find it difficult to perform these behaviours. Systematic reviews support the use of personal financial incentives to encourage healthy behaviours. There is concern that financial incentives may be unacceptable to the public, those delivering services and policymakers, but this has been poorly studied. Without widespread acceptability, financial incentives are unlikely to be widely implemented. We sought to answer two questions: what are the relative preferences of UK adults for attributes of financial incentives for healthy behaviours? Do preferences vary according to the respondents' socio-demographic characteristics? Methods We conducted an online discrete choice experiment. Participants were adult members of a market research panel living in the UK selected using quota sampling. Preferences were examined for financial incentives for: smoking cessation, regular physical activity, attendance for vaccination, and attendance for screening. Attributes of interest (and their levels) were: type of incentive (none, cash, shopping vouchers or lottery tickets); value of incentive (a continuous variable); schedule of incentive (same value each week, or value increases as behaviour change is sustained); other information provided (none, written information, face-to-face discussion, or both); and recipients (all eligible individuals, people living in low-income households, or pregnant women). Results Cash or shopping voucher incentives were preferred as much as, or more than, no incentive in all cases. Lower value incentives and those offered to all eligible individuals were preferred. Preferences for additional information provided alongside incentives varied between behaviours. Younger participants and men were more likely to prefer incentives. There were no clear differences in preference according to educational attainment. Conclusions Cash or shopping voucher-type financial incentives for healthy behaviours are not necessarily less acceptable than no incentives to UK adults.